Pressure–temperature–time constraints on gneiss dome formation in an intracontinental orogen. (15th October 2021) - Varga, Jan; Raimondo, Tom; Morrissey, Laura; Kelsey, David E.; Hand, Martin
Abstract : Abstract: The Entia Gneiss Complex represents the mid‐crustal core of the intracontinental Alice Springs Orogen. Located in the Harts Range, central Australia, it is characterized by the development of a domal structure including two sub‐domes separated by a steeply dipping median high‐strain zone. Dominantly, orthogneiss basement crops out through a structurally overlying cover sequence represented by the Harts Range Group and records evidence of hydration, recrystallization, and partial melting of precursor Paleoproterozoic granulite facies assemblages at amphibolite facies conditions. The structurally lowest parts of the Harts Range Group were metamorphosed to peak conditions of 10.5 kbar and ~880°C during rift‐related magmatism at 480–460 Ma, immediately prior to the onset of the Alice Springs Orogeny at 450–300 Ma. By contrast, the underlying Entia Gneiss Complex records widespread metamorphism and wet melting at upper amphibolite facies conditions. Phase equilibrium modelling and in situ LA–ICP–MS geochronology of rare, low‐variance kyanite–garnet‐bearing metapelites indicate that maximum P–T conditions of ~9 kbar and ~680°C were reached between c . 360–330 Ma, demonstrating a distinctive metamorphic and temporal evolution relative to the overlying Harts Range Group that can be linked to rheological stratification. Based on the integration of our results with existing monazite, zircon, and titanite geochronology, we interpret doming of the Entia Gneiss Complex to have involved compressive ascent of rheologically weakened crust below a region of extending upper crust near the termination of the Alice Springs Orogeny. In this way, the Harts Range Group represents a cooled, locally extending thrust sheet over ductile basement quasi‐concurrent with doming. Texturally‐late sillimanite combined with increasing Y content in monazite indicates high‐temperature, kyanite‐grade metamorphism was closely followed by decompression (3–4 kbar drop from peak conditions) and rapid cooling below 600°C during emplacement of the Entia Gneiss Complex at shallower crustal levels. The findings of this study highlight the feedback between hydration, retrogression, rheological weakening, and strain accommodation, thus allowing better evaluation of the thermomechanical history of gneiss dome formation within a narrow (<80 km wide) preconditioned intracontinental corridor. Highlights: First modern P–T–t framework for gneiss dome formation in the Entia Gneiss Complex, central Australia. The onset of metamorphism, partial melting and ductile flow at c . 360 Ma was catalysed by hydration of granulite facies basement during rift inversion. Rapid exhumation of partially molten crust from depths of >20 km is marked by fluid‐mediated resetting of monazite down to c . 310 Ma. Rheological stratification enabled and accelerated exhumation of the highest‐grade corridor of a narrow intracontinental orogen.